2013
DOI: 10.1517/14712598.2013.789856
|View full text |Cite
|
Sign up to set email alerts
|

Bapineuzumab and solanezumab for Alzheimer's disease: is the ‘amyloid cascade hypothesis' still alive?

Abstract: Phase III trials showed that bapineuzumab failed to improve cognitive and functional performances in AD patients, and was associated with a high incidence of amyloid-related imaging abnormalities (ARIA). Solanezumab's two Phase III trials in AD patients failed to meet endpoints when analyzed independently. However, analysis of pooled data from both trials showed a significant reduction in cognitive decline in mild AD patients. The improvement was associated with an increase in plasma amyloid-β (Aβ) levels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 67 publications
0
93
0
Order By: Relevance
“…The roles of these O-glycans are elusive, although it has been proposed that APP processing by a-secretase, b-secretase and c-secretase occurs after O-glycosylation of APP, and that O-glycosylated APP is preferentially secreted [26,29]. Interestingly, a recent report demonstrated a new type of tyrosine O-glycosylation on short (Ab [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] to Ab [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] but not on full-length (Ab 1-38 to Ab 1-42 ) Ab fragments [27]. In a study using CSF from AD patients and nondemented controls, an increase in the short Ab fragments carrying the tyrosine-linked glycan was observed in AD patients.…”
Section: App and Glycosylationmentioning
confidence: 99%
“…The roles of these O-glycans are elusive, although it has been proposed that APP processing by a-secretase, b-secretase and c-secretase occurs after O-glycosylation of APP, and that O-glycosylated APP is preferentially secreted [26,29]. Interestingly, a recent report demonstrated a new type of tyrosine O-glycosylation on short (Ab [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] to Ab [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] but not on full-length (Ab 1-38 to Ab 1-42 ) Ab fragments [27]. In a study using CSF from AD patients and nondemented controls, an increase in the short Ab fragments carrying the tyrosine-linked glycan was observed in AD patients.…”
Section: App and Glycosylationmentioning
confidence: 99%
“…The most promising current drug candidates are antibodies such as solanezumab that target various Aβ forms [136]. Solanezumab did not improve cognitive function in the two major phase 3 trials [137], but if one analyses the combined data there is a positive effect on cognition that should be explored further [138] [139].…”
Section: (X) Clinical Performancementioning
confidence: 99%
“…Although clinical trials of the Aβ-directed mAb Bapinezumab showed no clear cognitive benefits in patients with mild to moderate AD [42], the results also indicated that APOE ε4 carrier status may limit the response to anti-Aβ passive immunization [43,44], as well as being associated with an increased rate of microbleeds and vasogenic edema [45]. As the intention of upcoming clinical trials of Aβ-directed therapeutics is to target patients with early and prodromal AD [46,47], there is still a potential for differential responses to treatment among carriers of various APOE alleles.…”
Section: Discussionmentioning
confidence: 99%